Description of Bispira causioi sp. nov. (Annelida, Sabellidae), an introduced taxon or another case of native invasion? - GIANGRANDE, ADRIANA; TOSO, ANDREA; PUTIGNANO, MATTEO (Mediterranean Marine Science, 2026)
The new species Bispira causioi sp. nov. is here described. This taxon shares several morphological features, such as the shape of both uncini and companion chaetae, with other Bispira species mostly of tropical origin. The first observation of this taxon, along the Apulian coast, dates back to 2012 and was never recorded before. At the present, it occurs along the whole Italian Coasts, being reported in several pictures by the SCUBA-diving photographers and tentatively identified as either Sabella pavonina Savigny, 1822 or Bispira viola (Grube, 1863). In addition, in depth comparisons were conducted with material housed at the Museo di Biologia Marina of the Salento University, especially with the similar Mediterranean species (B. viola described by Grube 1863 for the North Adriatic Sea, as well as Bispira riccardi Giangrande, Putignano, Enrichetti 2022, described for North Tyrrhenian deep muddy substrates), but also with material of tropical Bispira species present in this collection. An extensive discussion on the literature concerning the reports of B. viola in the past precede the new species description, suggesting different interpretations for our findings.